Serelaxin Elicits Bronchodilation and Enhances β-Adrenoceptor-Mediated Airway Relaxation - Lam, Maggie; Royce, Simon G.; Donovan, Chantal; Jelinic, Maria; Parry, Laura J.; Samuel, Chrishan S.; Bourke, Jane E. (Frontiers in Pharmacology, 2016)
Treatment with β-adrenoceptor agonists does not fully overcome the symptoms associated with severe asthma. Serelaxin elicits potent uterine and vascular relaxation via its cognate receptor, RXFP1, and nitric oxide (NO) signaling, and is being clinically evaluated for the treatment of acute heart failure. However, its direct bronchodilator efficacy has yet to be explored. Tracheal rings were prepared from male Sprague-Dawley rats (250-350g) and tricolor guinea pigs, and precision cut lung slices (PCLS) containing intrapulmonary airways were prepared from rats only. Recombinant human serelaxin (rhRLX) alone and in combination with rosiglitazone (PPARγ agonist; recently described as a novel dilator) or β-adrenoceptor agonists (isoprenaline, salbutamol) were added either to pre-contracted airways, or before contraction with methacholine or endothelin-1. Regulation of rhRLX responses by epithelial removal, indomethacin (cyclooxygenase inhibitor), L-NAME (nitric oxide synthase inhibitor), SQ22536 (adenylate cyclase inhibitor) and ODQ (guanylate cyclase inhibitor) were also evaluated. Immunohistochemistry was used to localize RXFP1 to airway epithelium and smooth muscle. rhRLX elicited relaxation in rat trachea and PCLS, more slowly than rosiglitazone or isoprenaline, but potentiated relaxation to both these dilators. It markedly increased β-adrenoceptor agonist potency in guinea pig trachea. rhRLX, rosiglitazone and isoprenaline pretreatment also inhibited the development of rat tracheal contraction. Bronchoprotection by rhRLX increased with longer pre-incubation time, and was partially reduced by epithelial removal, indomethacin and/or L-NAME. SQ22536 and ODQ also partially inhibited rhRLX-mediated relaxation in both intact and epithelial-denuded trachea. RXFP1 expression in airway was at higher levels in epithelium than smooth muscle. In summary, rhRLX elicits large and small airway relaxation via epithelial-dependent and -independent mechanisms, likely via RXFP1 activation and generation of nitric oxide, prostaglandins and cAMP/cGMP. rhRLX also enhanced responsiveness to other dilators, suggesting its potential as an alternative or add-on therapy for severe asthma.